Accounting for Heritage Assets: Sustainability, Public Value, and Governance Challenges in Indonesia - Qimyatussa’adah Qimyatussa’adah; La Ode Abdullah; Nova Maulud Widodo (PT. ELSHAD TECHNOLOGY INDONESIA, 2026)
Heritage assets constitute irreplaceable public resources that embody historical, cultural, social, and environmental values and play a critical role in shaping national identity and supporting sustainable development. Despite their significance, the accounting treatment of heritage assets remains one of the most contested issues in public sector accounting, largely due to persistent valuation challenges, the dominance of non-financial values, and the absence of mandatory and harmonised international standards. These challenges are particularly pronounced in developing countries, where institutional capacity and accounting infrastructure are often constrained. This study examines the key challenges and opportunities associated with the application of accounting standards for heritage assets, with a particular focus on Indonesia as a developing country context. Employing a systematic literature review, the paper synthesises international academic research, public sector accounting standards, and regulatory frameworks related to heritage asset recognition, measurement, valuation, and disclosure. The analysis reveals that subjective valuation methods, limited availability of historical cost data, and the prioritisation of financial information over cultural, social, and environmental values continue to undermine transparency, accountability, and effective stewardship. At the same time, the findings highlight significant opportunities to enhance heritage asset reporting through adaptive harmonisation of international standards, strengthened non-financial disclosure, and sustainability-oriented reporting frameworks. By integrating financial and non-financial information, accounting can better support long-term conservation planning, public value creation, and intergenerational equity. This study contributes to the public sector accounting literature by repositioning heritage asset accounting as a governance and sustainability instrument rather than a purely technical exercise.